Deploiment of the national research and educational network "URAN" in the frame of the state program "information and connunication technology in education and science" for 2006-2010. - V.G. Galagan; M.R. Dombrougov; P.O. Zhuravkov; V.I. Timofeyev; Y.I. Yakimenko (Kherson State University, 2009)
It is shown results of connection of universities and scientific institutions to URAN network including optic fibers deployment in Ukrainian cities and URAN-GEANT 10 Gbps. It is discussed also means of providing of uninterruptable service to metropolitan area network users and implementation of network applied services.